Freshwater, climate change and adaptation in the Ganges River Basin - Hosterman, H.R.; McCornick, Peter G.; Kistin, E.J.; Sharma, Bharat R.; Bharati, Luna (IWA Publishing, 2012)
Climate change is one of the drivers of change in the Ganges River Basin, together with population growth, economic development and water management practices. These changing circumstances have a significant impact on key social and economic sectors of the basin, largely through changes in water quantity, quality and timing of availability. This paper evaluates the impact of water on changing circumstances in three sectors of the Ganges Basin – agriculture, ecosystems and energy. Given the inherent interconnectedness of these core sectors and the cross-cutting impact of changing circumstances on water resources, we argue that adaptation should not be viewed as a separate initiative, but rather as a goal and perspective incorporated into every level of planning and decision making. Adaptation to changing circumstances will need to be closely linked to water resource management and will require significant collaboration across the sectors.